2013
DOI: 10.1177/0300060513489799
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of neutrophil CD64 expression in neonatal infection: A meta-analysis

Abstract: Objective: The aim of the present study was to establish the predictive values of neutrophil CD64 expression in diagnosing neonatal infection. Methods: A comprehensive search of the PubMed and Embase Õ literature databases identified outcome data from published studies estimating the diagnostic accuracy of neutrophil CD64 expression for neonatal infection. Summary estimates for sensitivity, specificity, diagnostic odds ratios (DOR) and the area under the summary receiver operating characteristic curve (AUC) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…Neutrophils have been used as diagnostic tools in clinical settings: neutrophil absolute count (Wile et al, 2001;Pratt and Attia, 2007;Bressan et al, 2010;Manzano et al, 2011), enumeration of band neutrophils (band count) (Seebach et al, 1997;Al-Gwaiz and Babay, 2007), and the expression levels of neutrophil surface proteins (Nupponen et Rudensky et al, 2008;Dilli et al, 2010;Genel et al, 2012;Jia et al, 2013) to predict bacterial infections and severity outcomes. Due to the increasing evidence of neutrophils being involved in mediating viral diseases (Tumpey et al, 2005;Duffy et al, 2012), it is now possible to develop new diagnostic tools capable of distinguishing between viral and bacterial diseases.…”
Section: Neutrophils As a Tool To Distinguish Between Bacterial And Vmentioning
confidence: 99%
“…Neutrophils have been used as diagnostic tools in clinical settings: neutrophil absolute count (Wile et al, 2001;Pratt and Attia, 2007;Bressan et al, 2010;Manzano et al, 2011), enumeration of band neutrophils (band count) (Seebach et al, 1997;Al-Gwaiz and Babay, 2007), and the expression levels of neutrophil surface proteins (Nupponen et Rudensky et al, 2008;Dilli et al, 2010;Genel et al, 2012;Jia et al, 2013) to predict bacterial infections and severity outcomes. Due to the increasing evidence of neutrophils being involved in mediating viral diseases (Tumpey et al, 2005;Duffy et al, 2012), it is now possible to develop new diagnostic tools capable of distinguishing between viral and bacterial diseases.…”
Section: Neutrophils As a Tool To Distinguish Between Bacterial And Vmentioning
confidence: 99%
“…CD64, also known as FcgRI, is a Fc receptor of IgG, which is expressed on the surface of macrophages, monocytes, and eosinophils, but only a low expression is found on naïve neutrophils . Once pathogenic microorganisms irrupt into the body and activate neutrophils, a rapid increase in CD64 expression is detected.…”
Section: Discussionmentioning
confidence: 99%
“…6 CD64, also known as FcgRI, is a Fc receptor of IgG, which is expressed on the surface of macrophages, monocytes, and eosinophils, but only a low expression is found on naïve neutrophils. 7 Once pathogenic microorganisms irrupt into the body and activate neutrophils, a rapid increase in CD64 expression is detected. As a result of its early and rapid rise compared to other laboratory indications, such as CRP and WBCs, CD64 causes widespread concern among clinicians and scientists all over the world.…”
Section: Discussionmentioning
confidence: 99%
“…However, the diagnostic accuracy of nCD64 remains unclear due to the large range of sensitivity (0.26-0.95) and specificity (0.62-0.97) in different individual studies [6,7]. Although a meta-analysis has been conducted by Jia et al [8] they combined the results of median monocyte/ nCD64 ratio with nCD64 expression, which might be a source of heterogeneity. In addition, recently new individual studies [9,10] on this topic have reported conflicting results with Jia et al [8] Thus, there is a need to update the exploration.…”
mentioning
confidence: 99%
“…Although a meta-analysis has been conducted by Jia et al [8] they combined the results of median monocyte/ nCD64 ratio with nCD64 expression, which might be a source of heterogeneity. In addition, recently new individual studies [9,10] on this topic have reported conflicting results with Jia et al [8] Thus, there is a need to update the exploration. In this study, we performed to systematically evaluate the diagnostic performance of nCD64, neutrophil CD64 expression, white blood cell count, platelet count, IT ratio and C-reactive protein (CRP) in early diagnosis of neonatal sepsis.…”
mentioning
confidence: 99%